Inequality of learning amongst immigrant children in industrialised countries - Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2008)
Literature examining immigrants' educational disadvantage across countries focuses generally on average differences in educational outcomes between immigrants and natives disguising thereby that immigrants are a highly heterogeneous group. The aim of this paper is to examine educational inequalities among immigrants in eight high immigration countries: Australia, Canada, Germany, New Zealand, Sweden, Switzerland, UK and USA. Results indicate that for almost all countries immigrants' educational dispersion is considerably higher than for natives. For most countries higher educational dispersion derives from very low achieving immigrants. Quantile regression results reveal that at lower percentiles language skills impact more on educational achievement than at the top of the achievement distribution. Results are presented separately for immigrants of different age cohorts, varying time of immigrants' residence in the host country and subject examined (maths and reading) highlighting thereby the different patterns found by immigrant group and achievement measure.
Keywords: I21; 370; Education; educational inequalities; immigration; PISA; TIMSS; PIRLS; Migranten; Einwanderung; Bildungschancen; Soziale Ungleichheit; Bildungsniveau; Australien; Kanada; Deutschland; Neuseeland; Schweden; Schweiz; Großbritannien; USA